Kajian Faktor Penyebab Banjir dalam Perspektif Wilayah Sungai: Pembelajaran Dari Sub Sistem Drainase Sungai Beringin - Nugroho, Dody Adi; Handayani, Wiwandari (Jurnal Pembangunan Wilayah dan Kota, 2021)
Urbanization causes a shift in human activities and increases the occupancy of open spaces in the hilly areas of Semarang City. As a strategic area in the city of Semarang, Mijen and Ngaliyan Districts, which are the upstream and transition areas of the Beringin Drainage Sub-System, are experiencing economic and social growth. This then has an impact on the intensity of the floods that occur in Tugu District as its downstream area. This study aims to analyze the factors that cause flooding in the area of the Beringin Drainage Sub-System from a theoretical review to validate the results through interviews and field surveys. This study uses a qualitative descriptive analysis method by examining documents, research journals, books and maps and other related documents. From the results of the study, it can be concluded that the factors causing floods in the Beringin Drainage Sub-System area include changes in land use, rainfall and soil types, slope levels, erosion and sedimentation and inadequate capacity of the drainage system are phenomena and processes that are interrelated with one another. Strategic efforts are needed to anticipate flood events that occur almost annually in the Beringin Drainage Sub-System area.Â